The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.3389/fcimb.2020.563482
|View full text |Cite
|
Sign up to set email alerts
|

Carbapenem Resistant Aeromonas hydrophila Carrying blacphA7 Isolated From Two Solid Organ Transplant Patients

Abstract: Aeromonas hydrophila resides in a variety of aquatic environments. Infections with A. hydrophila mainly occur after contact with fresh or brackish water. Nosocomial infections with A. hydrophila can also occur. A. hydrophila infections can be difficult to treat due to both intrinsic and acquired antimicrobial resistance (AMR) mechanisms. In 2018-19, we isolated multi-drug resistant (MDR) A. hyrodphila from two solid organ transplant patients with intra-abdominal infections. We aimed to characterize their AMR m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 32 publications
1
10
0
Order By: Relevance
“…As a resultant, this led to increased resistance to carbapenems. The Aero28 isolate presented also showed resistance to the novel carbapenem-β-lactamase inhibitor combinations, suggesting that, unlike in Aero22, an induction of the cphA gene may have occurred ( 27 ). The absence of this gene led to the reduction of MIC to carbapenems observed in GES-7 and GES-16 transformants.…”
Section: Discussionmentioning
confidence: 99%
“…As a resultant, this led to increased resistance to carbapenems. The Aero28 isolate presented also showed resistance to the novel carbapenem-β-lactamase inhibitor combinations, suggesting that, unlike in Aero22, an induction of the cphA gene may have occurred ( 27 ). The absence of this gene led to the reduction of MIC to carbapenems observed in GES-7 and GES-16 transformants.…”
Section: Discussionmentioning
confidence: 99%
“…Human infections caused by Carbapenem resistant Aeromonas spp. have been reported in the recent past in Colombia and in United States [68,69]. Carbapenem resistance has been associated with the production of carbapenems hydrolyzing Aeromonas (CphA).…”
Section: Discussionmentioning
confidence: 99%
“…examined in this study could be that they intrinsically are encoded in the genomes. Despite so, suffice to point out that the MBL genes detected in this study have been reported from different bacteria species isolated from humans, animals, fish, chickens, mussel and the environments in different countries ( Maravić et al, 2013 ; Bottoni et al, 2015 ; Hilt et al, 2020 ; Ramsamy et al, 2020 ; Bertran et al, 2021 ; Wang Y. et al, 2021 ). Thus, it is likely that these AMR genes exist in other bacteria species in different aquatic environments and a wide range of host species in India.…”
Section: Discussionmentioning
confidence: 77%